A dance with dragons. Part II, After the feast - George R. R. Martin (Harper Voyager, 2012)
In King's Landing the Queen Regent, Cersei Lannister, awaits trial, abandoned by all those she trusted; while in the eastern city of Yunkai her brother Tyrion has been sold